Pengaruh Informasi Akuntansi, Persepsi Risiko dan Citra Perusahaan dalam Pengambilan Keputusan Investasi di Masa Pandemi Covid-19 - Fradella Anggraini; Erly Mulyani (Universitas Negeri Padang, 2022)
Investment decisions are policies used in the use of existing company funds on assets that are expected to provide future benefits with a certain level of risk. The purpose of this study was to determine whether accounting information, risk perception, and company image have a significant influence on investment decision making during the Covid-19 pandemic. This study uses quantitative research methods. The population in this study are investors who are registered in the BEI Investment Gallery, Faculty of Economics, Padang State University. The sample in this study used the Simple Random Sampling technique, the number of samples in this study was 110. The data was collected using questionnaires distributed online. The data were analyzed using descriptive analysis, Data Quality Test, Classical Assumption Test and Multiple Linear Regression Analysis. The results show that 1) accounting information influences investment decisions during the covid 19 pandemic, 2) risk perception affects investment decisions during the covid 19 pandemic, 3) company image affects investment decisions during the covid 19 pandemic. Based on the conclusions above, some suggestions can be given as follows: 1) For further researchers, it is expected to distinguish respondents who have become stock investors in the capital market or each who have not become investors, 2) It is hoped that further researchers will examine more deeply about the factors that influence investment decisions during the COVID-19 pandemic.